Religious and Cultural Constructions of Child Marriage: A Phenomenological Overview in Indonesia - Gita Anggraini; Fatimah Setiani (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
Child marriage is still a serious threat to the development of generations in Indonesia. This study aims to reveal the role of the construction of religious and cultural understanding in cases of child marriage in Tanah Mas Village, East Kotawaringin Regency, Central Kalimantan. The construction of religious and cultural understanding that is not comprehensive and partial can trigger child marriage behavior. This research is important to explore the roots of religious and cultural understanding, as well as construction in the families of perpetrators of child marriage in the community in order to rebuild (reconstruct) religious understanding that can prevent child marriage. This research used a qualitative descriptive method with a phenomenological approach. The research subjects were families of perpetrators of child marriage in Tanah Mas Sampit Village. The research was conducted from June to October 2024. Data collection was carried out using interviews, observation, documentation, and Forum Group Discussion. Analysis data was carried out using Cresswell's inductive analysis model. Data validity testing was carried out by triangulating data, extending observations, peer debriefing, and providing opportunities for other parties to provide input. The results showed that religious and cultural understanding are still the reasons for the high rate child marriage in Tanah Mas. In the aspect of religious understanding, the reason why parents immediately marry off their children is because they want to protect their children from acts that are forbidden by religion, their children's desire to be devoted to their parents, and their fear of falling into promiscuity. Meanwhile, in the cultural aspect, the habits of parents and family, the environment, and lack of access to education are the main reasons for child marriage. The social construction that occurs in the practice of child marriage at the research locus through the stages of externalization, objectification, and internalization that occur in the perpetrator's social environment